Serum Soluble Tumor Necrosis Factor Receptors 1 and 2 Are Early Prognosis Markers After ST-Segment Elevation Myocardial Infarction - Paccalet, Alexandre; Crola Da Silva, Claire; Mechtouff, Laura; Amaz, Camille; Varillon, Yvonne; de Bourguignon, Charles; Cartier, Regine; Prieur, Cyril; Tomasevic, Danka; Genot, Nathalie; Leboube, Simon; Derimay, François; et al. (Frontiers in Pharmacology, 2021)
Background: Inflammation following STEMI playing dual role, beneficial and deleterious, there is a need to find new biomarkers of STEMI severity. Objective: We hypothesized that the circulating concentration of the soluble receptors 1 and 2 of TNF-α (sTNFR1 and sTNFR2) might predict clinical outcomes in STEMI patients. Methods: We enrolled into a prospective cohort 251 consecutive STEMI patients referred to our hospital for PCI revascularization. Blood samples were collected at five time points: admission, 4, 24, 48 hours and 1 month after admission to assess sTNFR1 and sTNFR2 serum concentration. Patients underwent cardiac magnetic resonance imaging at one month. The study’s identifier in ClinicalTrials.gouv is: NCT03070496. Results: sTNFR1 concentration increased at 24 hours with a median of 580.5 pg/mL (95% confidence interval (CI) (534.4-645.6)). sTNFR2 increased at 48 hours with a median of 2244.0 pg/mL (CI (2090.0-2399.0). Both sTNFR1 and sTNFR2 peak levels were correlated with infarct size and left ventricular end diastolic volume and inversely correlated with left ventricular ejection fraction. Patients with sTNFR1 or sTNFR2 concentration above the median value were more likely to experience an adverse clinical event within 24 months after STEMI (hazard ratio (HR) at 8.8 [4.2-18.6], p<0.0001 for sTNFR1 and 6.1 [2.5-10.5], p=0.0003 for sTNFR2). Soluble sTNFR1 was an independent, and more powerful than troponin I (p=0.04 as compared to troponin AUC), predictor of MACCE. Conclusion: The circulating sTNFR1 and sTNFR2 are inflammatory markers of morphological and functional injury after STEMI. sTNFR1 appears as an early independent predictor of clinical outcomes in STEMI patients.